La violencia sexual en los procesos judiciales en los que se investigan crímenes de lesa humanidad, genocidio o crímenes de guerra - Kohan, Mariana (2016)
The aim of this work is to observe the role that sexual violence plays in processes of social domination (such as genocide, crimes against humanity and war crimes), in order to analyze how to legally address the sexual crimes that are committed in those contexts. In this interest, first a brief development of how this subject has been dealt with in international criminal law is carried out and finally the case of Argentina is analyzed.